The levels of base pay and incentive pay used by small firms to compensate professional employees with general and specific human capital. (2nd January 2022) - Chowdhury, Sanjib; Schulz, Eric
ABSTRACT: Drawing on human-capital theory, we propose divergent associations of professional employees' base pay and incentive pay with their levels of human capital in the small business context. Based on secondary data on 3, 750 professional employees representing 65 small firms, we found that, whereas human capital has a positive relationship with base pay, the relationship between human capital and incentive pay is less apparent. Specifically, we found that the relationship between incentive pay and position-specific experience is negative. Our findings suggest that small firms may use higher incentive pay to initially attract talent. Yet, the incentive pay does not grow as professional employees gain firm-specific experience. Moreover, the incentive pay significantly falls as professionals gain more position-specific experience, and this negative relationship is stronger in small firms with higher sales productivity. Further, firm longevity shows a moderately significant positive relationship with base pay; however, the findings show that firm longevity is negatively related to incentive pay.